2022
DOI: 10.32635/2176-9745.rbc.2022v68n4.2708
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de Vida de Sobreviventes de Câncer Onco-hematológicos Submetidos ao Transplante de Células-Tronco Hematopoiéticas: Revisão Integrativa da Literatura

Abstract: Introdução: Os avanços no tratamento relacionado ao câncer onco-hematológico têm resultado em um crescente número de pacientes submetidos ao transplante de células tronco-hematopoiéticas (TCTH) com êxito terapêutico, o que exige maior atenção com a qualidade de vida (QV) dos sobreviventes. Objetivo: Identificar a QV dos sobreviventes onco-hematológicos submetidos ao TCTH. Método: Revisão integrativa, entre 2011 a 2021, com busca nas bases de dados LILACS, MEDLINE, IBECS, SciELO e Biblioteca Cochrane. Utilizou-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Patients included in our study reported increased concerns about future fertility, both diagnosed with POF and those with residual function, and this will significantly impact present and future relationships. Comorbidities and medical conditions that may arise as short-or longterm complications of SCT, together with all other physical and psychological alterations related to initial disease and aggressive treatment, are well known to significantly impact a patient's well-being [36]. The decreased self-esteem associated with fertility issues and sexual dysfunctions, added to other possible transplant complications, will play a crucial role in the patient's recovery, social reintegration, personal and intimate relationships, and overall quality of life [6,12,37].…”
Section: Discussionmentioning
confidence: 99%
“…Patients included in our study reported increased concerns about future fertility, both diagnosed with POF and those with residual function, and this will significantly impact present and future relationships. Comorbidities and medical conditions that may arise as short-or longterm complications of SCT, together with all other physical and psychological alterations related to initial disease and aggressive treatment, are well known to significantly impact a patient's well-being [36]. The decreased self-esteem associated with fertility issues and sexual dysfunctions, added to other possible transplant complications, will play a crucial role in the patient's recovery, social reintegration, personal and intimate relationships, and overall quality of life [6,12,37].…”
Section: Discussionmentioning
confidence: 99%
“…Added to this is the complexity, complications and discomfort caused by the disease and therapy. Thus, there is the possibility of these abrupt changes interfering with individuals' social and emotional domain and making them susceptible to the development of common mental disorders (CMD) (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Soma-se a isso a complexidade, as intercorrências e o incômodo, causados pela doença e terapia. Assim, há a possibilidade de essas mudanças abruptas interferirem no domínio social e emocional do indivíduo e torná-lo suscetível ao desenvolvimento de transtornos mentais comuns (TMC) (6) .…”
Section: Introductionunclassified